2017
DOI: 10.1128/jvi.00542-17
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the K1L Gene Results in a Vaccinia Virus That Is Less Pathogenic Due to Muted Innate Immune Responses, yet Still Elicits Protective Immunity

Abstract: All viruses strategically alter the antiviral immune response to their benefit. The vaccinia virus (VACV) K1 protein has multiple immunomodulatory effects in tissue culture models of infection, including NF-B antagonism. However, the effect of K1 during animal infection is poorly understood. We determined that a K1L-less vaccinia virus (vΔK1L) was less pathogenic than wild-type VACV in intranasal and intradermal models of infection. Decreased pathogenicity was correlated with diminished virus replication in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
(130 reference statements)
0
12
0
Order By: Relevance
“…It is good for viral replication[180]C3L (VCP)Complement control protein (VCP)VCP modulates adaptive immune responses during infection[181, 182]C6Binds to STA2 and inhibits type I IFN signalingC6 is a dual function protein that inhibits the cellular responses to type I IFNs and as an inhibitor of IRF-3 activation[183]C7LAntagonizes IRF1-induced antiviral activitiesC7L inhibits antiviral activities induced by Type I interferons[184, 185]C12LBinds and inhibits IL-18C12L promotes virulence by reducing gamma interferon production and natural killer and T-cell activity[41, 186]E3LBinds dsRNA to block PKR activationE3 protein prevents the antiviral action of ISG15[187]F1LInhibits cytochrome CF1L promotes virulence by inhibiting inflammasome activation[188]K1LInhibits NF-κB activationK1L supports viral replication in human cells. Deletion of the gene led to a virus that is less pathogenic due to muted innate immune responses, yet still elicits protective immunity[39]K3LThe dsRNA-activated protein kinase (PKR) is inhibited by this pseudosubstrate inhibitorK3L prevents phosphorylation of e1F2α[189, 190]K7RPromotes histone methylation associated with heterochromatin associationK7R is a virulence gene; it inhibits the NF-κB pathway and thus the migration of neutrophil cells. It affects the acute immune response[37, 38, 191, 192]M1LAssociates with apoptosomeThe current model is that M1L associates with and allows the formation of the apoptosome, but prevents apoptotic functions of the apoptosome[193]N1LInhibits NF-κBN1L is a Bcl-2-like anti-apoptotic protein.…”
Section: Biology Of Vaccinia Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…It is good for viral replication[180]C3L (VCP)Complement control protein (VCP)VCP modulates adaptive immune responses during infection[181, 182]C6Binds to STA2 and inhibits type I IFN signalingC6 is a dual function protein that inhibits the cellular responses to type I IFNs and as an inhibitor of IRF-3 activation[183]C7LAntagonizes IRF1-induced antiviral activitiesC7L inhibits antiviral activities induced by Type I interferons[184, 185]C12LBinds and inhibits IL-18C12L promotes virulence by reducing gamma interferon production and natural killer and T-cell activity[41, 186]E3LBinds dsRNA to block PKR activationE3 protein prevents the antiviral action of ISG15[187]F1LInhibits cytochrome CF1L promotes virulence by inhibiting inflammasome activation[188]K1LInhibits NF-κB activationK1L supports viral replication in human cells. Deletion of the gene led to a virus that is less pathogenic due to muted innate immune responses, yet still elicits protective immunity[39]K3LThe dsRNA-activated protein kinase (PKR) is inhibited by this pseudosubstrate inhibitorK3L prevents phosphorylation of e1F2α[189, 190]K7RPromotes histone methylation associated with heterochromatin associationK7R is a virulence gene; it inhibits the NF-κB pathway and thus the migration of neutrophil cells. It affects the acute immune response[37, 38, 191, 192]M1LAssociates with apoptosomeThe current model is that M1L associates with and allows the formation of the apoptosome, but prevents apoptotic functions of the apoptosome[193]N1LInhibits NF-κBN1L is a Bcl-2-like anti-apoptotic protein.…”
Section: Biology Of Vaccinia Virusmentioning
confidence: 99%
“…This subsequently sponsors enhanced T cell responses against both the virus and any vector-encoded antigens [37, 38]. Shisler and colleagues showed that VV with a deletion of the K1L gene is less pathogenic, less immunogenic, and less capable of promoting immune cell infiltration in an intradermal model, yet it was still competent to elicit protective immunity [39]. In another study, the authors deleted the viral genes A44L, A46R, and C12L from the MVA genome.…”
Section: Biology Of Vaccinia Virusmentioning
confidence: 99%
“…A VACV WR mutant lacking K1 (vΔK1) replicated normally in cell culture but was attenuated in both intradermal and intranasal mouse models of infection [ 134 ]. Infection via the intranasal route induced less weight loss and lower virus titres compared to control viruses in primary (lungs) and secondary (spleen, brain) organs [ 134 ]. Despite producing smaller dermal lesions, vΔK1 replicated as well as wild-type and revertant controls and led to decreased immune cell infiltration and inflammatory gene expression.…”
Section: Vaccine Engineering By Targeting Vaccinia Virus Proteins mentioning
confidence: 99%
“…Despite producing smaller dermal lesions, vΔK1 replicated as well as wild-type and revertant controls and led to decreased immune cell infiltration and inflammatory gene expression. Nonetheless, compared to control viruses, intradermal infection with vΔK1 elicited the same levels of VACV-specific CD8 + T-cells and conferred the same protection against challenge with VACV WR [ 134 ]. The comparable immunological memory induced by vΔK1, despite the muted local inflammatory response, offers an opportunity to study the importance of the inflammatory response elicited by an attenuated vaccine for its protective efficacy [ 142 , 143 , 144 ].…”
Section: Vaccine Engineering By Targeting Vaccinia Virus Proteins mentioning
confidence: 99%
“…VACV strain WR encodes at least eight known or predicted ANK proteins, including 005-008 and 211-214 (Copenhagen B25 homologs), 014-017 (variola virus strain Bangladesh D8 homologs), 019 (Copenhagen C9 homolog), 030 (M1), 031 (K1), 186 (B4), 188 (B6), and 199 and 202 (B18) (32,33). However, only three of the WR ANK proteins (K1, B4, and B18) have reported functions (34)(35)(36)(37)(38)(39)(40)(41)(42). Thus, the study of the remaining ANK proteins is likely to uncover novel aspects of poxvirus biology.…”
mentioning
confidence: 99%